2009
DOI: 10.1186/1741-7007-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Genetical genomic determinants of alcohol consumption in rats and humans

Abstract: Background: We have used a genetical genomic approach, in conjunction with phenotypic analysis of alcohol consumption, to identify candidate genes that predispose to varying levels of alcohol intake by HXB/BXH recombinant inbred rat strains. In addition, in two populations of humans, we assessed genetic polymorphisms associated with alcohol consumption using a custom genotyping array for 1,350 single nucleotide polymorphisms (SNPs). Our goal was to ascertain whether our approach, which relies on statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(187 citation statements)
references
References 119 publications
(125 reference statements)
9
174
2
Order By: Relevance
“…Ethanol and/or IVM were co-applied with ATP for 20 s. Submaximal ATP concentrations that ranged from EC 5 to EC 10 were used in these studies that are designated as EC 10 throughout the manuscript. We have previously shown that ethanol inhibition of ATP function on P2X4Rs is more robust and reliable when tested in the presence of low concentrations of ATP (typically EC [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ) [11,13]. ATPactivated EC 10 responses were measured before and after each ethanol application to take into account possible shifts in the baseline current values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol and/or IVM were co-applied with ATP for 20 s. Submaximal ATP concentrations that ranged from EC 5 to EC 10 were used in these studies that are designated as EC 10 throughout the manuscript. We have previously shown that ethanol inhibition of ATP function on P2X4Rs is more robust and reliable when tested in the presence of low concentrations of ATP (typically EC [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ) [11,13]. ATPactivated EC 10 responses were measured before and after each ethanol application to take into account possible shifts in the baseline current values.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, they are inhibited by a broad range of ethanol concentrations beginning well below the concentrations considered legally intoxicating in the United States (0.08 % or 17 mM) [11][12][13][14][15][16][17]. Evidence from genetic and genomic studies [18,19] suggests that these receptors play a role in regulating ethanol intake.…”
Section: Introductionmentioning
confidence: 99%
“…The application of comprehensive, integrative approaches will define the future of alcohol research (Rodd et al, 2007;Tabakoff et al, 2009;Tapocik et al, 2013) and promises to be fruitful in elucidating the mechanisms underlying alcohol addiction. Genetic and biological studies in animal models or post-mortem human brain, with epidemiological and clinical surveys on human subjects, should be integrated with genomic data.…”
Section: Systems Biology and Integration Of Proteomics With Complemenmentioning
confidence: 99%
“…Of all the other substances of abuse, alcohol is by far the most harmful despite it being a legal drug (Nutt et al, 2010). Genetic, neurobiological, environmental, and psychosocial risk factors influence some individuals to develop compulsive and uncontrolled consumption of alcoholic beverages despite serious negative consequences (Koob and Le Moal, 2001;Koob, 2006;Mayfield et al, 2008;Phillips and Belknap, 2002;Potenza et al, 2011;Tabakoff et al, 2009). The molecular mechanisms underlying alcohol dependence involve different neurochemical systems and brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NIAAA intramural researcher Mark Egli argues that researchers' efforts might be better directed towards developing "rapid, inexpensive tests which yield the same information as the more elaborate models, although they may be less obvious models of alcoholism" (Egli 2005, 315). Others argue that experimental designs where the physiology and behavior of the animals strongly resembles human drinking can be used to identify novel genes or signaling pathways involved in drinking, which may point the way towards new drug targets or susceptibility genes in humans (Tabakoff et al 2009). …”
Section: Situating Animals In Valid Experimental Contextsmentioning
confidence: 99%